Incidence and clinical profile of coronary artery disease in patients with rheumatic heart disease undergoing valvular intervention - Nikhil Jadhav; Kamal H Sharma; Komal Shah; Ashwati Konat; Dhammdeep Humane; Sachin Patil (International Journal of Medical Research and Review, 2016)
Background: We aimed to determine the overall prevalence of coronary artery disease (CAD), atherosclerotic risk factors and clinical profile of patients with rheumatic heart disease (RHD) undergoing valvular interventions in Asian Indians.Method: This was an all comers, observational, prospective study of 757 rheumatic patients, who underwent coronary angiography (CAG) prior to percutaneous balloon valvulotomy, surgical valvular repair or replacement from July 2011 to December 2013. Among them who had significant CAD (stenosis ≥50%) (Group A), were compared with similar number of age and sex matched patients of RHD without CAD (Group B).Result: The overall prevalence of CAD in the patients undergoing valvular intervention was 9.1% (66.7% males, 33.3% female; mean age 55.20±8.6). The CAD incidence in patients with mitral, aortic and both valve replacement were 24.1%, 10.8% and 6.1% respectively. The prevalence of smoking habit (33.3% vs. 20.9%), diabetes (24.6% vs. 3.1%), hypertension (21.7% vs. 6.8%), postmenopausal status (65.2% vs. 18.4%), family history of CAD (17.4% vs. 8.3%) and aortic valve disease (10.1%) was significantly higher in group A as compared to group B except for obesity (11.5% vs. 18.7%).Conclusion: Prevalence of CAD in patients with valvular heart disease in western population of Asian Indians is 9.1%. Coronary angiography should be performed in patients having CAD risk factors, irrespective of the valvular lesion involved.